Working in hotels and catering - Wood, Roy C. (London, United Kingdom : International Thomson Business Press, 1997)
"Working in Hotels and Catering has been fully updated and revised to take account of changing student needs. It offers a comprehensive review of all the key topics relating to employment in the hospitality industry."
1. Sociology, work and the hospitality industry -- 2. Getting there: How to become a hospitality industry employee -- 3. Being there: pay and remuneration in hospitality services -- 4. Staying there? Organization, status and conflict in hotel and catering work -- 5. Occupations in the hospitality industry -- 6. Personnel management, labour turnover and the role of trade unions -- 7. De-skilling and work flexibility -- 8. International trends in employment -- 9. The future of hospitality work.
Includes bibliographical references and index.
Keywords: HOTEL MANAGEMENT